Interactive voice assistants – Does brand credibility assuage privacy risks? - Jain, Shilpi; Basu, Sriparna; Dwivedi, Yogesh K; Kaur, Sumeet (Journal of business research, 2022)
•Users prefer overall gains (value) over the perception of private data loss.•Brand credibility significantly moderates the relationship between VA features and the overall perceived value of VAs.•Higher Brand credibility reduces the perception of privacy risks.•Perceived privacy risks have a negative impact on the overall perceived value of voice assistants.•Utility features are favored over hedonic features contributing to overall perceived value and continued usage. Artificial intelligence-enabled conversational user interfaces, commonly known as voice assistants, are increasingly being used by individuals in their day-to-day lives to fulfill diverse needs (e.g. utility, hedonic, and social). However, the homeostatic (steadily present) attraction of the voice assistants is offset by the privacy risk concerns these devices present to users. Despite the growing literature on the adoption and usage of voice assistants, little has been said on whether brand credibility plays a mitigating role in assuaging the perception of privacy risk. This study combines both empirical and qualitative methods to shed light on the relationship between individuals’ perception of the overall value of voice assistants and their behavioral intention towards continued usage of voice assistants. A key study finding is that brand credibility significantly moderates the relationship between VA features and the overall perceived value of VAs – higher brand credibility reduces users’ perception of privacy risks.